Effect of prolonged starvation on the body preoperatively and the role of carbohydrate loading - Alhassoun, Abdulkarim Mohammad; Kammas, Fahad Hussain; Alaissawi, Mohammed Yousif; Hasan, Walaa Mohamed; Alrabiah, Nouf Mohammed; AlHarbi, Saja Butti; Alshahrani, Othman Mohammed; Kabli, Anas Sultan; Aljabr, Sami Abdullah; Aboshoushah, Enass Farouk; Alanazi, Mohammed Khaled; Alhassoun, Mohamad Abdulkarim (International Journal Of Community Medicine And Public Health, 2021)
Although recent reports discourage preoperative overnight fasting, many clinicians and surgeons still recommend 6-8 hours of overnight preoperative fasting before conducting elective surgeries. On the other hand, recent guidelines from worldwide multiple anesthesiology societies have suggested that overnight fasting should be approached with flexible durations and proper techniques. Many complications can result from prolonged fasting and preoperative starvation as the duration of fasting usually lasts for more than 12 hours secondary to intraoperative surgical delays. In this literature review, the aim was to discuss the current evidence from studies in the literature about the effect of preoperative starvation and the effect of carbohydrate (CHO) loading on the clinical outcomes of patients. We have noticed that gastric aspiration and respiratory damage can be prevented by preoperative fasting. However, this can lead to the development of other complications such as insulin resistance, a fierce immune response and exaggerated release of acute-phase reactants which might lead to severe organ damage and worsened patient’s prognosis. Accordingly, CHO loading should be carefully approached to properly intervene against these cases to enhance the prognosis of the prospective surgeries and the quality of care for patients.